Determination of HOMO and LUMO of [6,6]-Phenyl C61-butyric acid 3-Ethylthiophene Ester and poly (3-octyl-thiophene-2, 5-diyl) through voltametry characterization - Ashkan Shafiee; Muhamad Mat Salleh; Muhamad Yahaya (Universiti Kebangsaan Malaysia, 2011)
HOMO and LUMO of organic compounds are basic parameters for the design and fabrication of an organic solar cell. This paper presents a technique to obtain HOMO and LUMO of an n-type polymer of [6,6]-phenyl C61-butyric acid 3-ethylthiophene ester (PCBE) and a p-type polymer of poly (3-octyl-thiophene-2, 5-diyl) (P3OT). The energy of band gap for each material has been calculated using optical absorption spectrum. Cyclic Voltammetry was used to estimate the oxidation potential and energy band diagram consequently. The experiments were carried out in a three-electrode cell consisting of a platinum working electrode, a platinum counter electrode and a SCE reference electrode. P3OT showed energy band gap equal to 1.83 eV with HOMO and LUMO equal to 5.59 eV and 3.76 eV, respectively. PCBE showed energy band gap equal to 1.96 eV with HOMO and LUMO equal to 5.87 eV and 3.91 eV, respectively. Based on energy band diagram that was constructed from this experimental result, the couple materials may be successfully used to fabricate the feasible organic solar cells.